Tinjauan Pengelolaan Data Berbasis Digital Bagian Registrasi Pendaftaran Di RSUP Haji Adam Malik Medan - Puput Melati Hutauruk; Khairani (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
Data management is a data place that will become information which will later become health information. Where patient registration if done manually will be slow automatic management of data will have an impact on the quality of hospital services. Therefore digitization is required. The purpose of this study was to see how the implementation of digital-based data management at RSUP H. Adam Malik Medan. Subjects in this study were registration officers who entered 7 people, with the object being not 5M. This research was conducted with a descriptive method with a qualitative approach. Instrumentation of interview data and observation checklist. With the TOTAL 3 informants. The data analysis used in this research is descriptive qualitative to describe the implementation of data management. Based on the results of the research that there is no one who is not in accordance with the competence, the money is not yet available and adequate, the method is appropriate but has not worked well, the machine is not as expected while the material is in accordance with the competence. Suggestions from researchers are that officers should distribute leaflets (paper leaflets) to the public so that the public can register via cellphones (cellular) and that officers should change the internet speed to MBPS so that the registration process does not occur sluggishly.